The Presence of Vacuolated Kupffer Cells Raises a Clinical Suspicion of Niemann-Pick Disease Type C in Neonatal Cholestasis - Wang, Neng-Li; Chen, Lian; Lu, Yi; Xie, Xin-Bao; Lin, Jing; Abuduxikuer, Kuerbanjiang; Wang, Jian-She (Frontiers in Genetics, 2022)
Early diagnosing Niemann-Pick disease type C (NP-C) is still challenging, because splenomegaly is non-specific and oxysterol profiling studies also have a relatively low specificity for NP-C in neonatal cholestasis. This study explores an alternative, which can identify infants with a high clinical suspicion of NP-C in neonatal cholestasis. We reviewed the clinical findings of 9 neonatal cholestatic infants with NP-C diagnosed between January 2015 and December 2020. Seven underwent liver biopsy at ages ranging from 35 to 112 days. Foam cells were only detected in 2 (28.6%, 2/7) liver tissues obtained beyond 3 months of age. However, vacuolated Kupffer cells were detected in all 7 liver tissues: their amounts increased with age in the early disease course and their sizes became enlarged. Their significance was explored by using 168 neonatal cholestatic infants, who underwent genetic tests and liver biopsy between January 2018 and December 2020. Of them, 26 detected vacuolated Kupffer cells. Six (23.1%, 6/26) were diagnosed as NP-C, comparing to none of the 142 neonatal cholestatic infants without vacuolated Kupffer cells (2 =33.983, P <0.001). The ratio of positive diagnosis of NP-C was 31.6% (6/19) in neonatal cholestatic infants with both vacuolated Kupffer cells and splenomegaly. Therefore, we conclude that the presence of vacuolated Kupffer cells can raise a clinical suspicion of NP-C in neonatal cholestatic infants, especially in those with splenomegaly.